Walenty Skorochód-Majewski – kompetencje ekscentrycznego notariusza Księstwa Warszawskiego - Kanecki, Oskar (PRAWO i WIĘŹ, 2025)
Walenty Skorochód-Majewski (1764-1835), who was appointed a notary at the Court of Appeal in 1808, is a man who defies easy categorisation. On the one hand, he owed his office to merit; he ran a prosperous chancellery in a prominent location in the capital of the Duchy of Warsaw, enjoyed the esteem of its many inhabitants and was renowned for his knowledge of many foreign languages. On the other hand, his scholarly work was judged to be unprofessional and he himself to be completely absorbed in his idée fixe. This may have been the result of a lack of academic training. Almost as badly received was the result of Skorochód-Majewski’s translation of the French Code de commerce into Polish in 1808. However, this was the first translation of this legal text on Polish soil. Moreover, it only came into force a year later. However, the diligence and self-education of the notary, who sacrificed a considerable part of his fortune in the name of an idea, are unquestionable.